PENGARUH KENYAMANAN LAYANAN, CITRA MEREK, DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi pada Pelanggan Kantor Pos Indonesia di Wilayah Semarang) - Dyah Kusuma Al Afsyah; Suryono Budi Santosa (Diponegoro Journal of Management, 2022)
This study aims to see the effect of service convenience, brand image, and service quality on customer loyalty through customer satisfaction (study on Kantor Pos Indonesia service users in the Semarang Region). The population in this study are consumers who use the services of the Kantor Pos Indonesia. The number of samples used was 123 respondents who were selected using the purposive sampling method through questionnaires distributed online using google form. The data from this study were processed using SPSS version 26 The results of this study indicate that service convenience, brand image, and service quality have a positive and significant effect on customer satisfaction, and customer satisfaction has a positive and significant effect on customer loyalty.